Correction to: Identification of the meiotic toolkit in diatoms and exploration of meiosis-specific SPO11 and RAD51 homologs in the sexual species Pseudo-nitzschia multistriata and Seminavis robusta - Shrikant Patil; Sara Moeys; Peter von Dassow; Marie J. J. Huysman; Daniel Mapleson; Lieven De Veylder; Remo Sanges; Wim Vyverman; Marina Montresor; Maria Immacolata Ferrante (BMC Genomics, 2019)
Following the publication of this article [1], the authors reported that the link to Additional file 11 linked to the wrong set of data. The correct supplementary data is provided in this Correction article (Additional file 11).